STUDIES ON FIXED DOSE COMBINATION OF IBRUTINIB AND QUERCETIN SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEMS IN HUMAN CANCER CELL LINES (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Ibrutinib (IB), irreversibly inhibits Bruton’s Tyrosine Kinase which plays a crucial role in the tumor microenvironment and Quercetin (QC) shown apoptosis induction, angiogenesis inhibition, and anti-proliferative action against several human carcinoma cells. The self nano-emulsifying drug delivery system (SNEDDS) is suitable for the loading of insolubilized oil-based compounds such as Ibrutinib and Quercetin. In the current study IB with QC was formulated into SNEDDS and cytotoxicity was determined by using Human malignant melanoma (A-375) and Human lung adenocarcinoma (A549) cell lines. The optimized loaded formula consisted of Castor oil, Kolliphor® RH 40, and PEG-600. The optimized formulation was evaluated for physical parameters and the results were satisfactory. For cytotoxicity studies MTT assay was conducted for these combinations, IC50 values were calculated for the tested compound. In A-549 adenocarcinoma cell line, the calculated IC50 values (μM) for the test compounds T1 (pure IB+QC) and T2 (IB+QC SNEDDS) were 70.34+ 0.8 µM and 85.46 + 0.93 µM at 24 h study, respectively. In A-375 cancer cell line, IC50 values for the compounds T1 and T2 were 59.52 + 0.87 µM and 88.43 + 1.03 µM for 24 h study, respectively. It was observed that the IC50 of IB-QC loaded SNEDDS was higher than pure drug combination and these enter the cells by active transport and induce cytotoxicity to the cells. The overall results from the studies suggest that IB-QC-loaded SNEDD provided synergistic effects, which could play a significant role in the percentage of cell death.